Effects of long-term exposure to PM10 and NO2 on asthma and wheeze in a prospective birth cohort. Issue 1 (2nd September 2013) - Mölter, Anna; Agius, Raymond; de Vocht, Frank; Lindley, Sarah; Gerrard, William; Custovic, Adnan; Simpson, Angela
Abstract : Background: Epidemiological studies on the effect of urban air pollution on childhood asthma have shown conflicting results and so far no consistent association has emerged. However, a common limitation in previous studies has been exposure misclassification leading to uncertainties in risk estimates.The aim of this study was to analyse the effects of long-term exposure to particulate matter (PM10 ) and nitrogen dioxide (NO2 ) on the prevalence of asthma and wheeze within a population-based birth cohort—the Manchester Asthma and Allergy Study (MAAS). Methods: The prevalence of asthma and current wheeze within the cohort (N=1185) was determined through parental questionnaires at ages 3, 5, 8 and 11 years. The typical monthly PM10 and NO2 exposure of each child was estimated through a novel microenvironmental exposure model from birth to age 11. The association between exposure and asthma or wheeze was analysed using generalised estimating equations and multiple logistic regression. Results: The range of asthma prevalence was 15.2–23.3%, with the lowest prevalence at age 3 and the highest at age 5. The prevalence of current wheeze decreased from ages 3 to 8 (23.7–18%). The mean NO2 exposure decreased from the 1st year of life (21.7 µg/m 3 ) to the 11th year of life (16.0 µg/m 3 ). The mean PM10 exposure showed a smaller decrease (12.8 –10.7 µg/m 3 ). The statistical analysis showed no significant association between the exposures and either outcome. Conclusions: No evidence of a significant association between long-term exposure to PM10 and NO2 and the prevalence of either asthma or wheeze was found.